2021
DOI: 10.1016/j.jds.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of the second mesiobuccal canal in maxillary first molars among a sample of the Kurdistan Region-Iraq population - A retrospective cone-beam computed tomography evaluation

Abstract: Background/purpose One of the most complexes in root and canal anatomy is the maxillary first permanent molar. This study aimed to analyze the frequency of mesiobuccal (MB2) canal and its apical portals of exit, in patients belonging to different gender-age groups and determine the possible relation with sex and age. Materials and methods A CBCT scan images were accessed from a documented database of 343 patients (178 male, 165 female), who had an oral and maxillofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
2
9
0
1
Order By: Relevance
“…In the present study, there was no correlation between gender and the presence of MB2. This result is in agreement with those of Reis et al 32 Al‑Nazhan 25 and Zhang et al 34 In contrast, MB2 was shown to be predominant in males, as also reported by Al-Shehri et al 26 Faraj, 38 Ratanajirasut et al 39 and Kim et al 35 who found a relationship between gender and the number of canals. We also found no relationship between age and prevalence of MB2 canals.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, there was no correlation between gender and the presence of MB2. This result is in agreement with those of Reis et al 32 Al‑Nazhan 25 and Zhang et al 34 In contrast, MB2 was shown to be predominant in males, as also reported by Al-Shehri et al 26 Faraj, 38 Ratanajirasut et al 39 and Kim et al 35 who found a relationship between gender and the number of canals. We also found no relationship between age and prevalence of MB2 canals.…”
Section: Discussionsupporting
confidence: 92%
“…In a study performed by Martins et al looking at the worldwide prevalence of MB2 canals using CBCT, the overall prevalence was 73.8% [ 68 ]. Bentancourt P et al found 69.82% of MB2 canals in their study on 1100 maxillary molars using CBCT [ 69 ]. Even though the CBCT specifications changed across the studies, the Newtom CBCT scanner was the most commonly used scanner.…”
Section: Discussionmentioning
confidence: 99%
“…The MB 2 canal was found in 53.78% of the cases that means it was present in approximately half of the cases. 19 Another study on first maxillary molar teeth exhibited the highest prevalence of MB 2 canal, 92% and 87%, for right maxillary first molar and left maxillary first molar, respectively when CBCT was used. 20 In another retrospective study of 100 Dental CT, presence of MB 2 canal in maxillary molars were present in 57%.…”
Section: Resultsmentioning
confidence: 95%